Advanced Technologies, Systems, and Applications - Hadžikadić, Mirsad; Avdaković, Samir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume spans a wide range of technical disciplines and technologies, including complex systems, biomedical engineering, electrical engineering, energy, telecommunications, mechanical engineering, civil engineering, and computer science. The papers included in this volume were presented at the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT), held in Neum, Bosnia and Herzegovina on June 26 and 27, 2016. This highly interdisciplinary volume is devoted to various aspects and types of systems. Systems thinking is crucial for successfully building and understanding man-made, natural, and social systems. .
From the content: The Case for Interdisciplinary and Cross-disciplinary Exploration -- Systems Approach to Modeling and Simulation -- The role of service robots and robotic systems in the treatment of patients in medical institutions -- Analysis of Electroencephalogram on Children with Epilepsy Using Global Wavelet Spectrum -- Target Signatures and Pose Estimation -- multaneous Operation of Personal Computers and Mathematical Assessment of Their Harmonic Impact on the Grid -- Energy Efficient Public Lighting - A Case Study -- Analysis of a Load Profile of the Public Company Roads of Federation Bosnia and Herzegovina -- Standardization of Bosnia and Herzegovina- approaches today and the challenges of the future -- New Concept in the Design and Implementation of the Grounding Transmission Lines -- Solar and Wind Energy: EP B&H's Experiences on the Importance of Adequate Measurements. .
Keywords: Computational intelligence; Dynamics; Nonlinear theories; Biomedical engineering; Electric power production; Mechanical engineering; Computational Intelligence; Applied Dynamical Systems; Biomedical Engineering and Bioengineering; Electrical Power Engineering; Mechanical Power Engineering; Mechanical Engineering